Effect of Graphene Addition on Mechanical Properties of TiN - Shon, In-Tin; Yoon, Jin-Kook; Hong, Kyung-Tae (KOREAN INST METALS MATERIALS, 2017)
Despite of many attractive properties of TiN, the current concern about the TiN focuses on its low fracture toughness below the ductile-brittle transition temperature. To improve its mechanical properties, the approach generally utilized has been the addition of a second phase to form composites and to make nanostructured materials. In this respect, highly dense nanostructured TiN and TiN-graphene composites were obtained within two min at 1250 degrees C. The grain size of TiN was reduced remarkably by the addition of graphene. The addition of graphene to TiN simultaneously improved the fracture toughness and hardness of TiN-graphene composite due to refinement of TiN and deterring crack propagation by graphene. This study demonstrates that the graphene can be an effective reinforcing agent for improved hardness and fracture toughness of TiN composites.
Keywords: ACTIVATED SYNTHESIS; HARD MATERIALS; CONSOLIDATION